On a limit theorem of the renewal theory - Grigelionis, B. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. Григелионис, Об одной предельной теореме теории восстановления B. Grigelionis, Apie vieną atstatymo teorijos ribinę teoremą